Pengaruh Stabilitas Keuangan, Target Keuangan Tingkat Kinerja, Rasio Perputaran Aset, Keahlian Keuangan Komite Audit, dan Profitabilitas Terhadap Fraudulent Financial Statement - Mutiara Ayu Mindita Pratiya; Budi Susetyo (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2018)
The effect of financial stability, financial targets, level of performance, asset turnover ratio, audit committee's financial expertise, and profitability to fraudulent financial statement. Essay. Tegal : Faculty of Economics and Business. Pancasakti University Tegal 2018. This study aims to obtain empirical evidence and to analyze the effect of financial stability, financial targets, level of performance, asset turnover ratio, audit committee's financial expertise, and profitbility to fraudulent financial statement which measured using fraud score model (F-Score). The data in this research uses secondary data which form the company's financial statement and annual report. The population in this study are all companies listed on Indonesia Stock Exchange in period 20142017. This study uses purposive sampling method to select sample from the population and obtained sample of 28 companies of consumer goods industries. The methode of data analysis is performed with classic assumption test, descriptive statistics analysis and hypothesis tested by multiple linear regression analysis with SPSS version 23. The results of this study shows that the financial targets and level of performance significantly to the fraudulent financial statement, however the financial stability, asset turnover ratio, audit committee’s financial expertise, and profitability is not significant to the fraudulent financial statement. Financial stability, financial targets, level of performance, asset turnover ratio, audited financial audit, and profitability simultaneously have a significant effect on fraud financial statements.